2012
DOI: 10.1590/s0103-50532012000700009
|View full text |Cite
|
Sign up to set email alerts
|

Solvent extraction studies on uranium using amine based extractants and recovery from low grade ore leach liquors

Abstract: Neste estudo, extratores à base de amina (Alamine 336, Alamine 308, Alamine 304 e Aliquat 336) diluídos em querosene foram usados para extração de urânio e separação de outros elementos associados. Alamine 336 foi o melhor extrator para o processo de extração de urânio de soluções de sulfato quando comparado com outros reagentes à base de amina, Alamine 308, 304 Alamine 336 e Aliquat 336. O comportamento da extração sinérgica foi estudado com aminas como extratantes assim como reagentes sinergistas e organofos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Synergistic effects were also reported by mixing amine and organophosphorus acid [7][8][9][10][11][12][13]. For instance, Liu et al [10] showed synergistic extraction of rare-earth elements (REE) by mixing organophosphorus compounds such as Cyanex 272 (bis(2,4,4-trimethylpentyl)phosphinic acid), PC88A (2-ethylhexyl-2-ethylhexyl phosphonic acid) or D2EHPA (bis(2-ethylhexyl)phosphoric acid) with Alamine 336 (a blend of octyl and decyl tertiary amines).…”
Section: Introductionmentioning
confidence: 82%
“…Synergistic effects were also reported by mixing amine and organophosphorus acid [7][8][9][10][11][12][13]. For instance, Liu et al [10] showed synergistic extraction of rare-earth elements (REE) by mixing organophosphorus compounds such as Cyanex 272 (bis(2,4,4-trimethylpentyl)phosphinic acid), PC88A (2-ethylhexyl-2-ethylhexyl phosphonic acid) or D2EHPA (bis(2-ethylhexyl)phosphoric acid) with Alamine 336 (a blend of octyl and decyl tertiary amines).…”
Section: Introductionmentioning
confidence: 82%
“…The extraction behavior of new bi-functional ligands containing sulfur and amide groups towards the U(VI) ion from nitric acid was studied and reported [19][20][21][22][23][24] . Other reports are related to P based extractants used for U extraction [25][26][27][28][29] and our previous extraction studies on U extraction was developed and reported [30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [8] investigated solvent extraction of uranium using amine based extractants. Amine based extractants such as, Alamine 336, Alamine 308, Alamine 304 and Aliquat 336 in diluent kerosene were investigated.…”
Section: Introductionmentioning
confidence: 99%